The Impact of brain-gut microbiota composition on depression - Aleksander Ptasiński; Marta Targońska; Oskar Targoński; Adrianna Madej; Adrian Suława; Julia Furgalska; Sebastian Fedorowicz; Aneta Basiak; Rafał Niekurzak; Agnieszka Buczek (Quality in Sport)
Introduction and Purpose: Recently, depression has significantly marked its presence in both the scientific and social spheres due to its connections with suicides. According to WHO data, it affects approximately 280 million people and as much as 5% of all adults worldwide. The primary treatment for this condition includes drugs such as SSRIs and SNRIs. However, in the last decade, numerous studies have demonstrated the impact of gut bacteria dysbiosis on brain functions and, consequently, its role in the pathogenesis of depression. Therefore, this paper focuses on the mechanisms and factors that negatively or positively affect the state of gut microbiota leading to depression, as well as on modern intervention methods in this field. State of Knowledge: Recent clinical studies highlight that gut bacteria, in connection with the immune system, can influence brain function, including the pathogenesis of depression. According to scientists, this influence occurs through bacteria present in the gut, their metabolism, and its products. However, depending on the composition of the gut microbiota (i.e., bacterial taxa), the substances produced in the gut can have a positive or negative impact on brain function regulation, thus contributing to an increased risk of depression symptoms or to their alleviation and remission. Summary: This review paper describes the currently known factors that negatively or positively affect the maintenance of a healthy gut microbiota composition, their effectiveness in microbiome modulation, and potential methods for treating gut bacterial dysbiosis, which often coexists in patients suffering from depression. It is important to note the significant individual variability in the context of changes in the depressive microbiome and the response to various modification methods. Therefore, when selecting appropriate therapy, cooperation with the patient will be crucial to achieve satisfactory results and avoid adverse effects.